Dekonstruksi dan Rekonstruksi Epistemologi Pendidikan Agama Islam di Era Globalisasi - Iman Hendra Yani; Ahmad Sulhan (Mataram University, 2026)
The dominance of a transmissive-doctrinal paradigm in Islamic Religious Education has increasingly demonstrated its inadequacy in responding to contemporary pressures from digital disruption and value pluralism to religious extremism. This article aims to reconstruct the epistemological foundations of Islamic Education as a response to these structural challenges. Drawing on critical library-based analysis, the study examines classical and contemporary educational thought alongside recent empirical studies in Islamic pedagogy. Data were collected through systematic documentation of scholarly literature and analyzed using content analysis and critical discourse analysis. Sources were selected based on their relevance to epistemological critique and reconstructive frameworks within Islamic education. The study identifies three structural flaws in prevailing Islamic education epistemology: the colonial-era bifurcation of religious and general knowledge; the hegemony of text-centred transmission at the expense of contextual reasoning; and the absence of a transformative-emancipatory orientation. Against these deficiencies, the study advances a four-pillar reconstructive model grounded in (1) an integrative framework bridging naqliyyah and aqliyyah traditions, (2) maqasid al-syariah teleology foregrounding the protection of intellect and social harmony, (3) a Qur'anically-rooted critical pedagogy centred on tafakkur and tadabbur, and (4) values-based multicultural education anchored in rahmatan lil 'alamin. Empirical studies indicate that Islamic education models emphasising critical thinking demonstrate higher outcomes in student moral reasoning and civic engagement. Epistemological reconstruction is therefore a non-negotiable precondition for cultivating Muslim learners who are critically literate and spiritually resilient.